Vectors for construction of translational fusions to beta-galactosidase - D. EBBOLE (Fungal Genetics Reports, 1990)
The use of lacZ as a reporter gene requires appropriate plasmid constructions to produce fusions of fungal promoter and translations initiation sequences to the E. coli lacZ gene. I have constructed three plasmids which may facilitate construction of lacZ fusions.